Determinan Kinerja Karyawan Coffee shop di Semarang Tengah - Dea, Widya Putri Nareswari; Almira Santi Samasta; Diana Aqmala; Febrianur Ibnu Fitroh Sukono Putra (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
The growth of the coffee shop industry in Central Semarang shows rapid dynamics along with changes in people's lifestyles and increased coffee consumption among the younger generation. This condition requires coffee shop s to not only rely on product quality, but also maximize the role of human resources, especially employees, as the spearhead of service. However, fluctuations in employee performance are still a challenge that needs to be studied more deeply. This study aims to analyze the influence of job satisfaction, workload, and Work life balance on the performance of coffee shop employees in Central Semarang. The method used is quantitative with a survey approach, using a questionnaire as a data collection instrument distributed via Google Form. The sample consisted of 160 coffee shop employees selected using census technique. The results showed that job satisfaction and work life balance had a positive and significant effect on employee performance, while workload had a negative and significant effect. This research is expected to be a reference for coffee shop managers in designing more appropriate and sustainable human resource management strategies.